Simulating the process of compacting the railway bed - Karsakova , Akbope; Kadyrov, Adil; Pak, Igor; Kyzylbayeva, Elvira (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The article solves the problem of the interaction between sealing plate and the railway bed. Numerical results have been obtained in the process of three-dimensional modeling using the finite element method, which allow demonstrating volumetrically the stress-strain state of the railway bed and using it in the calculation methodology.